The effect of competence and discipline on work motivation and impact on employee performance of Pratama tax office in Malang Utara - Heriyanto, Tri; Naser, Jamal Abdul; Setia, Kohar Adi (MEC-J (Management and Economics Journal), 2018)
Employee performance of Pratama Tax Office at North Malang was affected by competence, discipline and work motivation to serve taxpayers. Therefore, this study will examine the effect of competence and discipline on work motivation and the impact on employee performance. This research was conducted at Pratama Tax Office at North Malang. The samples were 92 respondents. Data was collected using a questionnaire and completed by respondents themselves. The obtained data was analyzed by path analysis to determine the effect of each variable. This study produced seven findings. First, Competence directly affects on Work Motivation. Second, Discipline directly affects on Work Motivation. Third, Competence directly affects on Employee Performance. Fourth, discipline directly affects on employee performance. Fifth, work motivation directly affect on employee performance. Sixth, Competence indirectly affect on employee performance mediated by work motivation. Seventh, Discipline indirectly affect on employee performance mediated by work motivation